Apelin and APJ regulation in adipose tissue and skeletal muscle of type 2 diabetic mice and humans - Dray, Cédric; Debard, Cyrille; Jager, Jennifer; Disse, Emmanuel; Daviaud, Danièle; Martin, Pascal; Attané, Camille; Wanecq, Estelle; Guigné, Charlotte; Bost, Frédéric; Tanti, Jean-François; Laville, Martine; et al. (American journal of physiology: endocrinology and metabolism, 2010)
Apelin, an adipocyte-secreted factor upregulated by insulin, is increased in adipose tissue (AT) and plasma with obesity. Apelin was recently identified as a new player in the control of glucose homeostasis. However, the regulation of apelin and APJ (apelin receptor) expression in skeletal muscle in relation to insulin resistance or type 2 diabetes is not known. Thus we studied apelin and APJ expression in AT and muscle in different mice models of obesity and in type 2 diabetic patients. In insulin-resistant high-fat (HF)-fed mice, apelin and APJ expression were increased in AT compared with control. This was not the case in AT of highly insulin-resistant db/ db mice. In skeletal muscle, apelin expression was similar in control and HF-fed mice and decreased in db/ db mice. APJ expression was decreased in both HF-fed and db/ db mice. Control subjects and type 2 diabetic patients were subjected to a hyperinsulinemic-euglycemic clamp, and tissues biopsies were obtained before and at the end of the clamp. There was no significant difference in basal apelin and APJ expression in AT and muscle between control and diabetic patients. However, apelin plasma levels were significantly increased in diabetic patients. During the clamp, hyperinsulinemia increased apelin and APJ expression in AT of control but not in diabetic subjects. In muscle, only APJ mRNA levels were increased in control but also in diabetic patients. Taken together, these data show that apelin and APJ expression in mice and humans is regulated in a tissue-dependent manner and according to the severity of insulin resistance.